IDENTIFIKASI MORFOLOGI KAWASAN PESISIR PANTAI DI KOTA SEMARANG DAN PERKEMBANGANNYA (STUDI KASUS : PANTAI MARINA) - Tiasa Adimagistra; Wahjoerini Wahjoerini (Indonesian Journal of Spatial Planning, 2020)
The city and its development is one of the complex things that occurs in the arrangement of spatial activities. The city's shape and dynamic city developments are influenced by physical and non-physical aspects such as social, economic, cultural, and technological evolving over time and following human needs. The change in the city form called the morphology of the city will never finish and become perfect such as building architecture, circulation system, open space, and urban infrastructure facilities. The city's morphological approach in identifying and identifying the shape of the city is not only covering the physical appearance, but also involves non-physical elements that contribute to the process of changing the city.The city of Semarang as a big city in Java Island is included in the coastal areas whose morphological development from time to time is very dynamic which grows expanding to the surrounding area. It is no exception at Marina Beach which located at PRPP Complex, Tawangsari district. This area is a residential development and settlement area planned by the developer and is now an important area for the economic growth of Semarang, with the new international airport, the airport Ahmad Yani International So this area is interesting to do a study of morphological identification and how it develops. The purpose of this research is to identify the morphology and architecture of the city in the coastal areas of Semarang in the pre-independence period, post-independence to the present. The step that will be done is to identify the pattern of the Marina coastal area based on satellite imagery and then three methods of analysis, namely the historical analysis of the region, the analysis of the area pattern, the analysis of the City room product City image analysis, townscape analysis, and building style analysis and building type. From the results of the analysis will be conducted morphological identification and how the development of coastal areas of Semarang especially in Marina beach.